A Review on the Antibacterial Property of Curcuma longa L. - Sonali Ray (Research Perspectives of Microbiology and Biotechnology Vol. 1, 2024)
The utilization of herbal products as therapeutics and nutraceuticals is becoming more prevalent in today’s world. Novel medicinal plants with their natural biomolecules are being analysed to provide effective alternative to the synthetic chemical drugs being used in disease treatments. The present review is a comprehensive enumeration of the reports of antibacterial potential of turmeric - Curcuma longa L., which also has a number of other various pharmacological activities. The significant pharmacological properties of the plant are by virtue of the polyphenolic compounds, curcumin. The investigations already done by different workers have emphasized the remarkable potential of turmeric extract, both aqueous and alcoholic, to inhibit bacterial growth. The essential oil extract of the rhizome and leaves of turmeric have been reported to show remarkable inhibitory effect on a wide spectrum of gram-positive and gram-negative bacteria. This plant proved to be a promising candidate for usage as an antibacterial product in many endodontic treatment cases. The evidences provided in this review would encourage more experimental approaches regarding the antibacterial activity of C. longa in diverse fields using modern techniques like nanotechnology.